Bilateral platelet rich plasma injections with assisted techniques for temporomandibular joint disorders - Simsek, Muhammed Eren (The European Research Journal, 2016)
Objectives. Temporomandibular joint (TMJ) disorders are frequently encountered in the population. Pain is the most common complaint. TMJ luxation needs surgical treatment which has many risks. The objective of this study was to treat TMJ disorders with a minimal invasive method, platelet rich plasma (PRP) injection, instead of surgery. Methods. The study included 7 female patients aged 15 to 42 years. Three ml (2 ml into the joint capsule and 1 ml into the pericapsular region) injections were applied in both sides. Two sessions of injections were planned. Three months after the last injection, a questionnaire was carried out. Results. Six of the subjects underwent two injections, and one of them underwent only one injection. Verbal analogue scale score was 7.66±1.3 before the injections, 5.33±2 after the first injection, and 3.33±1.2 after the second injection. Pain decreased significantly after the first and more significantly after the second injection (p=0.017 and p<0.001, respectively). The mean total satisfaction rate was two at the first step (p>0.05) and four at the second step (p=0.017). Conclusions. Findings of our study indicate that PRP may be a useful technique for treatment of TMJ subluxations. The significant reduction in pain after either one or two injections suggests that it might be reasonable to investigate the efficacy and safety of this technique in larger study populations.